Influence Literacy Finance and Inclusion Finance To Sustainability Performance of MSMEs in Denpasar City With Behavior Finance As an Intervening Variable - Ni Putu Trisna Windika Pratiwi; Cokorda Gde Bayu Putra; Ni Ketut Muliati; Putu Cita Ayu; Ni Putu Yeni Yuliantari (Universitas Pendidikan Nasional, 2025)
Recession economy is threats faced by many countries , esp after various turmoil economy global Which happen in a number of decade Lastly , the sustainability of Micro , Small, and Medium Enterprises (MSMEs) is key in support economy local , especially in the middle global challenges such as predicted recession occurred in 2025. Research This aim for analyze influence financial literacy and financial inclusion to performance sustainability of MSMEs with financial behavior as intervening variable. population in study This is MSME actors who run business in Denpasar City with amount 32,776 units business. method taking samples in research This is probability sampling with technique Proportionate Stratified Random sampling ie techniques used when population have members / elements that are not homogeneous and stratified in a way proportional , with amount sample as many as 100 MSME actors in Denpasar City . Method data analysis used in study This that is apply method Structural Equation Model based Partial Least Square (PLS) with help SmartPLS. Research results state that in a way partial financial literacy and financial inclusion influential positive and significant to financial behavior. In terms of partial financial literacy, financial inclusion, and financial behavior influential positive and significant to performance sustainability of MSMEs. For effect mediation, results study state that financial behavior capable mediate influence financial literacy and financial inclusion to performance sustainability of MSMEs.